2017
DOI: 10.1021/acs.macromol.7b01524
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Majority Charge Carrier from Hole to Electron by Incorporation of Cyano Groups in Diketopyrrolopyrrole-Based Polymers

Abstract: A thienylene−vinylene−thienylene (TVT) derivative with cyano groups in the 3-and 3′-positions was synthesized as a building block of semiconducting polymers for high mobility organic field effect transistors (OFETs). (E)-1,2-Di-(3-cyanothiophen-2-yl)ethene (2CNTVT) was copolymerized with diketopyrrolopyrrole (DPP) units via Stille coupling reaction to give 2DPP-2CNTVT and 7DPP-2CNTVT. The properties of these two polymers were compared with those of the corresponding polymers without cyano groups in TVT (2DPP-T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
71
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(72 citation statements)
references
References 26 publications
(46 reference statements)
0
71
0
Order By: Relevance
“…Subsequently, Kim et al confirmed the nitrile group's effect on the DPP‐based copolymer with the same backbone structure of P45 . They introduced a nitrile group at the 3‐position of the TVT unit ( P46 ) and obtained a μ e value of 1.2 cm 2 V −1 s −1 …”
Section: Molecular Design Strategies For High‐performance D–a‐conjugamentioning
confidence: 96%
“…Subsequently, Kim et al confirmed the nitrile group's effect on the DPP‐based copolymer with the same backbone structure of P45 . They introduced a nitrile group at the 3‐position of the TVT unit ( P46 ) and obtained a μ e value of 1.2 cm 2 V −1 s −1 …”
Section: Molecular Design Strategies For High‐performance D–a‐conjugamentioning
confidence: 96%
“…A DPP‐based conjugated polymer using a novel variation of the TVT comonomer was reported Kim et al By introducing electron‐deficient cyano groups at the 3‐positions of the thiophenes of the TFT monomer, they were able to convert a predominantly p‐type polymer into one that produced n‐type OTFTs, presumably because they lowered the LUMO, which in turn facilitated electron injection. The authors also compared alkyl chain spacer length and found that this did not affect n‐type mobility values, with both C1 ( P33 ) and C6 spacer distances reported to have given the same average electron mobility values.…”
Section: N‐type Organic Semiconductorsmentioning
confidence: 99%
“…Cyano is a strong EWG, which can significantly lower the HOMO and LUMO energy levels. 67,68 Cyano substitution may cause obvious steric hindrance because of its bulky size. This steric hindrance effect can lead to a twisted backbone, which is harmful for p-conjugate and intermolecular p-p stacking.…”
Section: Cyano Substitutionmentioning
confidence: 99%